2016
DOI: 10.1653/024.099.0439
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila suzukii(Diptera: Drosophilidae) Arrives at Minas Gerais State, a Main Strawberry Production Region in Brazil

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
22
0
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 10 publications
0
22
0
2
Order By: Relevance
“…It has been found in Europe and North America (Walsh et al, 2011;Cini et al, 2012Cini et al, , 2014Asplen et al, 2015); and recently, it has also been found in South America expanding its distribution in this continent (Bitner-Mathé et al, 2014;Deprá et al, 2014;dos Santos, 2014;Paula et al, 2014;Vilela & Mori, 2014;González et al, 2015;Santadino et al, 2015;Santos Geisler et al, 2015;Andreazza et al, 2016;Wollmann et al, 2016;Lue et al, 2017). Out of the approximately 1200 species that belong to the genus Drosophila, only three species, D. suzukii, D. pulchrella Tan, Hsu &Sheng, 1949, andD.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…It has been found in Europe and North America (Walsh et al, 2011;Cini et al, 2012Cini et al, , 2014Asplen et al, 2015); and recently, it has also been found in South America expanding its distribution in this continent (Bitner-Mathé et al, 2014;Deprá et al, 2014;dos Santos, 2014;Paula et al, 2014;Vilela & Mori, 2014;González et al, 2015;Santadino et al, 2015;Santos Geisler et al, 2015;Andreazza et al, 2016;Wollmann et al, 2016;Lue et al, 2017). Out of the approximately 1200 species that belong to the genus Drosophila, only three species, D. suzukii, D. pulchrella Tan, Hsu &Sheng, 1949, andD.…”
mentioning
confidence: 98%
“…2 Calculated as the percentage of D. suzukii over the total of drosophilids sampled. González et al (2015), Santadino et al (2015), Santos Geisler et al (2015), Andreazza et al (2016), Wollmann et al (2016), and Lue et al (2017).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the global production of strawberries, as observed for fields of other soft‐skinned fruits, recent invasions of the spotted‐wing drosophila , Drosophila suzukii (Matsumura) (Diptera: Drosophilidae), have elevated these flies to one of the most prevalent strawberry pests . However, despite recent efforts aimed at developing other management strategies, e.g., potential parasitoids, mass trapping and physical exclusion (netting), the application of synthetic insecticides remains the most used tool for the management of D. suzukii , , .…”
Section: Introductionmentioning
confidence: 99%
“…A partir de 2013, esta mosca foi detectada no Brasil (primeiro no sul e mais tarde nas regiões sudeste), Argentina, Chile e Uruguai. A chegada à América do Sul desta mosca, que ataca tanto espécies de plantas exóticas cultivadas quanto de espécies nativas, é alarmante (Deprá et al, 2014;González et al, 2014;Medinamuñoz et al, 2015;Andreazza et al, 2016Andreazza et al, , 2017a. Diferentemente de outros drosofilídeos que atacam principalmente frutas podres ou danificadas, D. suzukii ataca frutos maduros em sua maioria de pele macia, como bagas e cerejas, causando perdas econômicas por danos físicos diretos, além de proporcionar condições para infecções secundárias por outros insetos ou agentes patogênicos (Mitsui et al, 2006;Walsh et al, 2011;Loriatti et al, 2017).…”
Section: Introductionunclassified